Is Oncidium poikilostalix an invasive species? Population ecology and reproductive behavior of this epiphytic orchid in Chiapas, Mexico - García-González, Alfredo; Riverón-Giró, Frander Brian; Damon, Anne; Raventós, José; Aguilar-Romero, Osiris (Instituto de Ecología, A.C., 2018)
Background and Aims: Biological invasions are considered as second to habitat loss as a cause of the extinction of species. The study of population dynamics is particularly relevant for species with expansive behavior. The aims of this study were to: (1) evaluate the population ecology of Oncidium poikilostalix in shaded coffee plantations in Mexico, (2) evaluate the reproductive behavior of O. poikilostalix in this habitat, and (3) determine whether this orchid should be considered as an invasive species.Methods: During 2013-2015, most of the individuals of the Mexican population of O. poikilostalix (located south of the state Chiapas) were marked and measured. Additionally, the flower and fruit production (first flowering and repeated flowering), mortality and recruitment of new individuals were registered annually, and its potential distribution was modeled.Key results: Within this period a population increase of 1.11% was observed, with a proportional increase in the number of flowers and fruits. There was a strong correlation between the leaf area of individuals and the production of flower spikes (R=0.690, p<0.001) and flowers (R=0.775, p<0.001). The number of mature individuals that had repeated flowering varied from 47.1% in 2013 to 22.5% in 2015. There was also correlation between the leaf area of individuals with the fact that they do not flower, flower once and repeated flowering (X2=277.65, p<0.001). The Mexican population of O. poikilostalix is located on the northern limit of the potential distribution of this species.Conclusions: It is unlikely that O. poikilostalix behaves as an invasive species. Despite being a locally abundant taxon, with an apparently healthy population established in traditional shaded coffee plantations, its distribution in Mexico is limited, which may represent a serious risk to its survival in the country.